Bio-ethanol steam reforming on Ni/Al2O3 catalyst - Comas, Jose Luis (2004)
In this work, the ethanol steam reforming on Ni/ Al2O3 catalyst at temperatures between 573 and 773 K was studied and an overall reaction scheme as a function of temperature was proposed. It can be concluded that higher water/ethanol ratio (6:1) and higher temperature (773 K) promote hydrogen production (91% selectivity). Over Ni-based catalyst there would not be evidences that water gas shift reaction occurs. The presence of oxygen in the feed produces a favorable effect on carbon deposition; nevertheless the carbon monoxide production is not reduced.